Contribution to knowledge of the genus Cuanta Dworakowska, 1993 (Hemiptera: Cicadellidae: Typhlocybinae) with descriptions of three new species - Kang, Juxia; Huang, Min; Yang, Yuru; Zhang, Yalin (Zootaxa, 2018)
The leafhopper genus Cuanta Dworakowska, 1993 is recorded from China for the first time. Three species, C. plana, C. curva. and C. centralis spp. nov., are described and illustrated as new to science. A check-list and key to all species of Cuanta are provided.